2016
DOI: 10.1590/0100-3984.2015.0018
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced hypopharyngeal squamous cell carcinoma: single-institution outcomes in a cohort of patients curatively treated either with or without larynx preservation

Abstract: ObjectiveThe present study was aimed at describing a single-institution experience in the curative treatment of patients diagnosed with locally advanced hypopharyngeal squamous cell carcinoma.Materials and MethodsData concerning all patients treated for locally advanced hypopharyngeal squamous cell carcinoma between January 2006 and June 2012 were reviewed.ResultsA total of 144 patients were included in the present study. The median follow-up period was 36.6 months. Median survival was 26 months, and 2-year an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…The systematic review included 2 randomised controlled trials 11 , 33 and 11 observational studies 9 , 26 , 27 , 34 41 . A thorough search of PubMed and Medline, Embase, Scopus, the Cochrane Library, and Google Scholar yielded 5639 citations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The systematic review included 2 randomised controlled trials 11 , 33 and 11 observational studies 9 , 26 , 27 , 34 41 . A thorough search of PubMed and Medline, Embase, Scopus, the Cochrane Library, and Google Scholar yielded 5639 citations.…”
Section: Resultsmentioning
confidence: 99%
“…All 11 non-randomised studies were retrospective observational studies that were published in English 9 , 26 , 27 , 34 41 . All studies with the exception of two reported data only on advanced stage hypopharyngeal cancer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations